Analisis Perbandingan Komitmen Bidan Koordinator dalam Pencatatan dan Pelaporan PWS KIA di Kabupaten Kapuas - Kristie Hapsari Primaharini; Sutopo Patria Jati; Mateus Sakundarno Adi (Jurnal Manajemen Kesehatan Indonesia, 2020)
The midwife's commitment in recording the PWS KIA is a form of responsibility in reporting the PWS KIA and contributing to the achievement of the PWS KIA target. The lack of data and information on PWS KIA can lead to achievement of low and not low targets and cause PWS KIA problems to be resolved. Observation results of the PWS KIA Kapuas report found problems, namely; the report is incomplete, only partially filled in, even the number of formats sent is different for each puskesmas.This research is a qualitative research. Methods of data collection using questionnaires, observation of documents and in-depth interviews. The object of this study was the coordinating midwife and the Head of the Yankesdas Section as the person in charge of PWS KIA in Kapuas Regency.The results of the study are of 2 categories: coordinator midwives with "high commitment" of 17 health centers and "low commitment" of 9 health centers. Midwife coordinator with high commitment supported, among others; long work experience, has the attitude and responsibility for the trust that was stabbed, SK was appointed as a coordinating midwife, had a SOP supporting document PWS KIA report, received support from kapus and coworkers as well as the monev from the Kapuas District Health Office where the condition was not obtained from coordinating midwives with "low commitment". It is recommended to increase support for all coordinating midwives in the recording and reporting of PWS KIA in the form of supervision of the Kapuas District Health Office with quality activities, both the time and the material delivered.Keywords: Commitment, Midwife Koordinaor, PWS KIA